ВЛИЯНИЕ ВЕЩЕСТВА НА ОСНОВЕ ФИБРОИНА ШЕЛКА НА ПОКАЗАТЕЛИ ЛИПИДНОГО ОБМЕНА У КРЫС С ЭКСПЕРИМЕНТАЛЬНОЙ ГИПЕРХОЛЕСТЕРИНЕМИЕЙ (World Science, 2018)
The article presents the results of a study on the effectiveness of a substance based on silk fibroin, obtained at the Institute of Chemistry and Polymer Physics of the Academy of Sciences of the Republic of Uzbekistan, in eliminating disorders of lipid metabolism in the body. In experiments in rats with experimental hypercholesterolemia, the substance was found to have a cholesterol-lowering property, which is manifested by a decrease in cholesterol level both in blood and in tissues. Studies on the mechanism of the hypocholesterolemic effect of the studied substance have shown its effects on the enterohepatic pathway of bile acids, which makes it possible to classify this substance as a group of bile acid sequestrants.